Exploring the future(s) of South East Asia: Four scenarios for agriculture and food security, livelihoods and environments - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2014)
The CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS), the FAO Economics and Policy Innovations for Climate-smart Agriculture (EPIC) Programme and UNEP/WCMC coordinated their activities in Southeast Asia in 2013 and beyond in order to develop and quantify participatory scenarios on the future of Food Security, Environments and Livelihood for three primary countries, the Kingdom of Cambodia, the Lao People’s Democratic Republic and Viet Nam. The workshop was co-funded by the FAO EPIC program and by CCAFS Southeast Asia. A regional workshop was organized in November 2013 in Ha Long with around 30 participants from the region during three days the participants developed qualitative scenarios on the future of Food Security, Environment and Livelihoods in the SEA region.